A produção em área da agricultura familiar e sua vinculação com o agronegócio : estudo de caso do PA Carimã em Rondonópolis/MT - Silva, Sálvio Itamar da (2015)
This work has as study object the PA Carimã, settlement created by INCRA in 1997 and located in the municipality of Rondonópolis / MT. Aims to understand the relationships established among family settled farmers and agribusiness, the site has characteristics that set it apart, as the existence of two areas whose physical characteristics are uneven and that directly influence production. Another distinguishing element is the presence in all surrounding properties geared toward agribusiness, this activity characterized by dependence and use of technical and scientific innovations, making scientific and informational advance the agribusiness base. The PA is carrying a dubious landscape, sometimes analogous to the surroundings, sometimes jarring that. To establish the links of family farming with agribusiness, the method used was the exploratory research to collect data and quantitative and qualitative analysis of the data later this data was analyzed based on the reasoned theoretical framework in the productive space circuit and circle cooperation to check the links between these productive areas as diverse.